Pengaruh Motivasi terhadap Kinerja Pegawai Kecamatan Penukal (Pali) Melalui Employee Engagement - Anjasmara Anjasmara; Muji Gunarto (J-MAS (Jurnal Manajemen dan Sains), 2022)
Employees have an important role in achieving company goals. Objectives in this research to know the motivation of the employee performance in the office of subdistrict tripe district pali through employee engagement. The public in this study population the office of subdistrict of tripe kaupaten Pali, large sample of the research is 50 officials in the office of subdistrict of tripe sub-district Pali. This study using primary data obtained from the questionnaire and analysis techniques used was a SEM. The result of the research indicated that the impact on the employee performance, employee engagement influences the employee performance, effect on employee motivation engagemen, employee engagement mediate influence motivation for the employee performance in the office of subdistrict tripe district pali 2022 years.